Residential Neighborhood and Quality of Life Assessment: An Analytical Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study focuses on the quality of life among the local population in the residential neighborhood and comes up with proposals that will improve the quality of social and economic life where it shows the satisfaction of the population about the quality of urban life in residential neighborhood in the new Baghdad area in the section of Al-Rusafa in Baghdad and the study relied on the descriptive method based on the method of social survey in sample where the study found that the quality of urban life of the concepts of the hour where the planners and academics who developed many indicators to assess the quality of life , whether within the housing unit or at the level of the residential neighborhood especially after the accumulations and dichotomies of housing units and problems resulting from residential and urban policies that care about the quantum at the expense of quality that meet the needs of the moment related mainly to the elimination of the housing crisis without paying attention to quality within these communities where it was found that most of the population is dissatisfied with their residential conditions in terms of community services as well as collecting waste and disposal and in order to raise the level of quality of life within the residential locality, the research sees the need to provide the necessary services for housing and take into account the increase in the population to achieve user satisfaction on services and the government must Creating jobs by investing in the public and private sectors to increase income and the possibility of increasing quality of life.